2010
DOI: 10.1007/s11842-010-9135-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Climate Change Through Small-Scale Forestry in the USA: Opportunities and Challenges

Abstract: Forest management for carbon sequestration is a low-cost, low-technology, relatively easy way to help mitigate global climate change that can be adopted now while additional long-term solutions are developed. Carbon-oriented management of forests also offers forest owners an opportunity to obtain a new source of income, and commonly has environmental co-benefits. The USA is developing climate change policy that recognizes forestry as a source of offsets in carbon markets, and the emissions trading programs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…We considered the influence of project duration on the viability of carbon farming, as it is clear that in addition to policy risk and market uncertainty, long-term contracts can present a significant barrier to private landholder participation (Ando and Chen, 2011;Charnley et al, 2010;Mitchell et al, 2012). In our analysis, we found that the total area viable for carbon farming and the annual economic returns over a 25 year project duration did not differ substantially to what was expected over 100 years.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We considered the influence of project duration on the viability of carbon farming, as it is clear that in addition to policy risk and market uncertainty, long-term contracts can present a significant barrier to private landholder participation (Ando and Chen, 2011;Charnley et al, 2010;Mitchell et al, 2012). In our analysis, we found that the total area viable for carbon farming and the annual economic returns over a 25 year project duration did not differ substantially to what was expected over 100 years.…”
Section: Discussionmentioning
confidence: 87%
“…Monitoring costs could be reduced by undertaking measurements of carbon stocks at longer intervals (Cacho et al, 2012). Carbon farming offers considerable economies of scale (Cacho et al, 2013;Charnley et al, 2010) which we have not accounted for here. While some establishment and management costs are proportional to project size (tube stock, pest management), many components of market participation and transaction costs are fixed.…”
Section: Discussionmentioning
confidence: 99%
“…These land use and management approaches include afforestation, reforestation, and avoided deforestation as well as improved management of forests, grasslands, and rangelands (Gibbon et al 2010). In many cases, projects that aim to improve terrestrial carbon storage through land management are seen as having the potential to provide biodiversity and livelihood cobenefits (Bekessy & Wintle 2008;Venter et al 2009;Charnley et al 2010;Strassburg et al 2010). However, carbon-oriented land management faces a number of challenges (Agrawal et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of sample designs have been used (Ravindranath and Ostwald 2008) and protocols for verifying and monitoring carbon offset programs established (Brown 1999). Inventory costs are often one of the barriers for many landowners (Charnley et al 2010). Subsampling schemes are frequently used in forest inventories because they increase sample efficiency and decrease sample costs (Bell et al 1983;Iles 2003;Kershaw et al 2016).…”
Section: Discussionmentioning
confidence: 99%